'As long as it's good': An intergenerational family perspective of bridging gaps between reality and ideality of second couplehood as a problem and as a solution. Issue 4 (13th January 2015) - KOREN, CHAYA; SIMHI, SHIRAN
ABSTRACT: Second couplehood in old age following widowhood or divorce is a phenomenon developing with the increase in life expectancy and is yet to be accepted as part of the normative ageing process. The aim of this paper is to examine how family members of three generations perceive second couplehood in old age as a new phenomenon within a changing society and a dynamic family structure. The multigenerational families of 19 second-couplehood dyads (a total of 38 multigenerational families) were recruited using criterion sampling. The second-couplehood dyads were composed of men who repartnered at age 65+ and women at 60+, with children and grandchildren from a lifelong marriage. We tape recorded and transcribed verbatim 107 semi-structured qualitative interviews with older partners, their adult children and grandchildren. Analysis was based on grounded theory and dyadic-analysis principles adapted to families. Two main themes were found that presented gaps between reality and ideality experienced by the participants regarding second couplehood: as a problem through its disadvantages, and as a solution through its advantages. The gaps in both themes were bridged by the account: 'as long as it's good'. Findings are discussed in the context of modernisation theory, the lifecourse and the family lifecycle perspectives relating to changes in family structure and ambivalence and how to deal with them on the macro, mezzo and micro levels.